(untitled) (Research, Society and Development, 2021)
Based on data from China, where the pandemic originated, cardiac injury has become a prominent feature of the disease, affecting up to 30% of patients and helping 40% of deaths. Several cardiovascular complications have been described, such as myocardial injury (20% of cases), arrhythmias (16%), myocarditis (10%), in addition to heart failure (HF) and shock (up to 5% of cases). The aim of this work is to inform and describe the new myocarditis caused by the new virus. And demonstrate the importance for further studies related to the new disease. All publications that have data on the new myocarditis in patients with the new SARS-CoV-2, scientific publications, official from the World Health Organization and government, between a certain date (2019-2021) were used. Approximately 500 articles were found, languages were checked, and if it was really about the theme of the new myocarditis related to the new virus, then 39 articles were obtained for the discussion. Myocardial injury, signaled by markers, was evidenced in the first cases of the disease. The National Health Council of China demonstrated in a report, 12% of patients without cardiovascular problems. Thus, since SARS-CoV-1 and SARS-CoV-2 reach cells through the angiotensin-converting enzyme 2, where this possibly also happens in patients infected with the new virus. However, more research is still needed to prove these possible theories.